45‐4: Near‐eye Foveated Display for Achieving Human Visual Acuity. Issue 1 (29th May 2019) - Tan, Guanjun; Lee, Yun-Han; Zhan, Tao; Yang, Jilin; Liu, Sheng; Zhao, Dongfeng; Wu, Shin-Tson
Abstract : We demonstrate a multi‐resolution foveated display, to achieve retina‐level angular resolution while keeping wide field‐of‐view (FOV), with two display panels and an optical combiner. The first panel provides a wide FOV and the second one offers an ultra‐high resolution for the central fovea region, by an optical minifying system which enhances the effective resolution by up to 5×. Moreover, a switchable Pancharatnam‐Berry phase deflector is employed to actively shift the high‐resolution region to enable eye‐tracking. The proposed design can effectively suppress pixelation and screen‐door effect in near‐eye displays.